Appraisal of the Deqi Concept among Contemporary Chinese Acupuncturists. (2nd October 2013) - Chen, Sheng; Guo, Shengnan; Marmori, Federico; Wang, Yanping; Zhao, Qi; Wang, Baokai; Ha, Eunhae; Miao, Yanhuan; Xiang, Li; Zhao, Mingwen; Huo, Yuwei; Nan, Yinan; et al.
Abstract : Deqi, an important component of the traditional theory of acupuncture and moxibustion, is the key factor in determining clinical therapeutic effect of acupuncture. In this paper, based on the digging up, arrangement, and in-depth analysis of the famous contemporary Chinese acupuncturists' perspectives of deqi, the authors summarize the concept and manifestation, as well as the properties of deqi, and correlativity of deqi with acupuncture manipulation through reviewing modern clinical research. Proposals for more scientific and standardized acupuncture research are introduced to reexamine and restore the implication of deqi in combination with the clinical practice.